Individual heterogeneity, group interaction, and co-operative behaviour: evidence from a common-pool resource experiment in South Africa and Namibia - Bernd Hayo; Björn Vollan (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
We present econometric evidence on the influence of an individual’s sociodemographic characteristics, economic background, and dynamic personal and group interactions on co-operative behaviour in a social dilemma situation. The data are from a framed common-pool resource experiment conducted in Namibian and South African farming communities. Our paper helps to better understand the discrepancy between the fact that people seem to care about advancing their relative position in real life but tend to act to reduce inequality in a laboratory setting. We analyse the first move in the game, the cumulated amount of resources gained by the players and, by taking into account the temporal dimension of the game in a panel context, each individual move.
Keywords: 330